Analysis of Success Factors for Multi-Stakeholder Based Residential Projects in Padang Pariaman Regency - Syofyan, Irfan Andika; Hidayat, Benny; Suraji, Akhmad (CIVED, 2023)
Padang pariaman district is one of potential region to develop being residence and settlement. From 2018 until these days, the subsidized housing is the dominated housing which been realised to be distributed for the low income community. Behind the developments, obstacles will be certainly faced by developers on the project fluidity. The adversity on building permits with stakeholder and developer deficiency of expertise are factors causing the housing project failure. This study purposes on discovering the success factor of housing project from perspectives of each stakeholder. The method of the study is mix methods. The study concludes that there are some successes factors of housing project based on perspective of each stakeholder. There is the commitment factor from the government institution perspective. While from the developer perspective, there are factors such as location, building quality, company management and guaranty. From consumer perspective, it associates with housing location, housing facility, housing quality and guaranty from developer. The dominant factor from the questionnaires’s result is the housing quality factor, so this can achive great influence category from the consumers.